Influence of environmental temperature on nitrogen retention apparent digestibility of protein and amino acids and energy balance in growing pigs - Fialho, Elias T.; Cline, Tilford R. (Pesquisa Agropecuaria Brasileira, 1991)
Thirty crossbred, castrated male pigs weighing 32 kg were assigned to one of five experimental ambient temperatures (11°, 17°, 23°, 29° and 35°C). The pigs were housed randomly and individually in steel metabolism cages in temperature controlled rooms. The animals were fed according to their metabolic size and the methodology utilized was total feces and urine collection. The data were analyzed using regression analysis. The estimated values of apparent digestibility of dry matter and protein, nitrogen retention, net protein utilization and biological value increased as environmental temperature increased to 29°C, but decreased above this temperature. Both low (11° and 17°C) and high (35°C) temperatures decreased all of the parameters analyzed. Apparent digestibility of amino acids showed the same effect and was highest at 29°C and lowest at 11°C and 35°C. Digestible energy and metabolizable energy values showed that the efficiency of energy utilization increased as environmental temperature increased. It was determined that DE and ME were maximized at 26° and 27°C respectively. The results suggest that temperatures fall between 25° and 29°C are within the thermoneutral zone of 32 kg pigs kept in metabolism cages.